2016
DOI: 10.1177/2325957416680294
|View full text |Cite
|
Sign up to set email alerts
|

Conservative Treatment of Chronic Subdural Hematoma in HIV-Associated Thrombocytopenia with Tranexamic Acid

Abstract: Chronic subdural hematomas (CSDHs) and its management comprise a majority work in a neurosurgical specialty. The effectiveness of surgery is beyond doubt and sometimes even lifesaving in severe cases. However, the straightforward surgery is sometimes complicated by the associated comorbidities of the patient. Comorbidities in the form of coagulopathies secondary to chronic liver diseases, drugs (warfarin, ecosprin, clopidogrel), thrombocytopenia secondary to systemic illness are always a challenge to deal with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Tanweer et al 5 described 14 patients with TXA after surgery for cSDH of whom none experienced a recurrence or complication. Kutty et al 6 and Moscote-Salazar 9 each described one patient with primary TXA treatment for cSDH and complete resolution of het cSDH. Mikkelsen et al 10 described one patient with five recurrences for which surgical intervention was performed.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tanweer et al 5 described 14 patients with TXA after surgery for cSDH of whom none experienced a recurrence or complication. Kutty et al 6 and Moscote-Salazar 9 each described one patient with primary TXA treatment for cSDH and complete resolution of het cSDH. Mikkelsen et al 10 described one patient with five recurrences for which surgical intervention was performed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of tranexamic acid (TXA), an antifibrinolytic agent, has been described in several reports, with quite positive results. [3][4][5][6][7][8][9][10] Recently, we started a double-blind, placebo-controlled, multicenter, randomized clinical trial in the Netherlands, the TORCHstudy (Tranexamic Acid to Prevent Operation in Chronic Subdural Hematoma), 11 to assess the efficacy of TXA to prevent surgery for patients diagnosed with cSDH for which a conservative treatment is selected as a primary treatment strategy. Here we describe the results of off-label TXA treatment in seven patients, in anticipation to this trial.…”
Section: Introductionmentioning
confidence: 99%
“…Antifibrinolytic drugs can stop bleeding by inhibiting plasminogen activation and plasminogen activity. Clinical case reports and retrospective studies have shown that tranexamic acid, as an antifibrinolytic drug, can be used to treat CSDH, promote hematoma absorption, and reduce recurrence [49][50][51][52][53]. However, some studies believed that antifibrinolytic drugs could increase the incidence of thrombotic events in patients [54].…”
Section: Hemostasis and Antifibrinolytic Therapy Of Chronic Subdural Hematomamentioning
confidence: 99%
“…10) There were several other studies reporting the successful role of TXA as a primary treatment of CSDH or as a salvage medication at CSDH recurrence. 12,14,16,26) Recent studies have reported that TXA administration delayed the CSDH recurrence and reduced hematoma volume faster. 27,28) Although randomized trials are ongoing to reveal the efficacy of TXA, the role of TXA as an adjunctive medical treatment still lacks evidence.…”
Section: Introductionmentioning
confidence: 99%